TRANS-ARTERIAL EMBOLIZATION WITH N-BUTYL CYANOACRYLATE GLUE FOR RENAL BLEEDING: Case Report - Young, Benny (BALI MEDICAL JOURNAL, 2014)
Background: The objectivity in management of renal bleeding is to preserve a significant renal parenchyma tissue and prevent associated morbidities like anemic shock or renal impairment from substantial nephron demise or obstructed uropathy. Trans-arterial embolization therapy by interventional radiology offers a high success rate with potential of reserving normal renal tissue. The selection material for renal arterial embolization largely depends on vasculature anatomy and endpoint of procedure. N-butyl cyanoacrylate glue in our experience is applied in lesion supplied by small size of end-artery.